The Implementation of Accrual Accounting in Lithuania’s Public Sector: Retrospective Assessment of the Challenges - Timukaitė, Greta; Šalienė, Asta (Buhalterinės apskaitos teorija ir praktika, 2025)
The article analyses the reform of the Lithuanian public sector accounting system, with an emphasis on the transition from cash-based to accrual-based accounting based on International Public Sector Accounting Standards (IPSAS). The study examines the stages of the reform and the challenges encountered, including the lack of qualified personnel, complex legal systems and insufficient technological infrastructure. Based on a literature review and qualitative expert interviews, the study finds that external pressures - EU policy, IPSAS recommendations, and internal motivation - led to the initiation of the reform. Although the long-term benefits of the reform are evident, the study highlights persistent systemic challenges, including gaps in legal alignment with the accrual basis, uneven technological readiness, and varying levels of accounting professionals’ competence. Therefore, to ensure the sustainability and effectiveness of accrual-based public sector accounting in Lithuania, it is essential to further develop the legal and institutional framework, continuously enhance professional development, and strengthen inter-institutional cooperation. The article contributes to the international discourse on public sector accounting harmonisation by providing a detailed, context-specific case study of the Lithuanian experience.